2006
DOI: 10.5713/ajas.2007.153
|View full text |Cite
|
Sign up to set email alerts
|

Expression of B Cell Activating Factor Pathway Genes in Mouse Mammary Gland

Abstract: In our previous study, overexpression of extracellular proteinase inhibitor (Expi) gene accelerated apoptosis of mammary epithelial cells, and induced expression of B cell activating factor (BAFF) gene. In this study, we found induction of BAFFreceptor (BAFF-R) gene expression in the Expi-transfected cells. A proliferation-inducing ligand (APRIL) gene is another TNF family member and the closest known relative of BAFF. We found induction of APRIL gene expression in the Expi-overexpressed apoptotic cells. NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…However, it has only recently been demonstrated that adult muscle satellite cells are capable of converting to non-myogenic lineages. Treatment of myogenic satellite cells with rosiglitazone or adipogenic inducers/ciglitizone converts these cells into osteogenic or adipogenic cells (Jin et al, 2006;Kook et al, 2006;Singh et al, 2006;Choi et al, 2007). Though, the differentiation of myoblasts and satellite cells to adipoblast for intramuscular adipogenesis have been reported in mammals (Van Barneveld, 2003;Schoonmaker et al, 2004) but the potential inter-relationship of these cells in differentiating to another lineage have not been put forth.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has only recently been demonstrated that adult muscle satellite cells are capable of converting to non-myogenic lineages. Treatment of myogenic satellite cells with rosiglitazone or adipogenic inducers/ciglitizone converts these cells into osteogenic or adipogenic cells (Jin et al, 2006;Kook et al, 2006;Singh et al, 2006;Choi et al, 2007). Though, the differentiation of myoblasts and satellite cells to adipoblast for intramuscular adipogenesis have been reported in mammals (Van Barneveld, 2003;Schoonmaker et al, 2004) but the potential inter-relationship of these cells in differentiating to another lineage have not been put forth.…”
Section: Introductionmentioning
confidence: 99%